Supply chain evolution: theory, concepts and science - MacCarthy, Bart L.; Blome, Constantin; Olhager, Jan; Srai, Jagjit Singh; Zhao, Xiande (Emerald, 2016)
The supply chain landscape is changing. New supply chains emerge and evolve for a variety of reasons. In this paper we examine the nature of new and changing supply chains and their influences, and address the broad question “What makes a supply chain like it is?”. The paper highlights and develops key aspects, concepts, and principal themes concerning the emergence and evolution of supply chains over their life cycle. We identify six factors that interact and may affect a supply chain over its life cycle. A number of emergent themes and propositions on factors affecting a supply chain’s characteristics over its life cycle are presented. We argue that a new science is needed to investigate and understand the supply chain life cycle. Supply chains are essential to the world economy and to modern life. Understanding the supply chain life cycle and how supply chains may evolve provides fresh perspectives on contemporary supply chain management. The paper presents detailed reflections from leading researchers on emerging, evolving and mature supply chains.